Protection of Iron-Induced Oxidative Damage in Neuroblastoma (SH-SY5Y) Cells by Combination of 1-(N-Acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one and Green Tea Extract - Nittaya Chansiw; Kanokwan Kulprachakarn; Narisara Paradee; Adchara Prommaban; Somdet Srichairatanakool (Bioinorganic Chemistry and Applications)
Iron is a crucial trace element and essential for many cellular processes; however, excessive iron accumulation can induce oxidative stress and cell damage. Neurodegenerative disorders, such as Alzheimer’s disease and Parkinson’s disease, have been associated with altered iron homoeostasis causing altered iron distribution and accumulation in brain tissue. This study aims to investigate the protective effect of 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) in combination with green tea extract (GTE) on iron-induced oxidative stress in neuroblastoma (SH-SY5Y) cells. Cells were cultured in medium with or without ferric chloride loading. Their viability and mitochondrial activity were assessed using MTT and JC-1 staining methods. Levels of the cellular labile iron pool (LIP), reactive oxygen species (ROS), and lipid-peroxidation products were determined using calcein acetoxymethyl ester, 2′,7′-dichlorohydrofluorescein diacetate, and TBARS-based assays, respectively. The viability of iron-loaded cells was found to be significantly increased after treatment with CM1 (10 µM) for 24 h. CM1 co-treatment with GTE resulted in a greater protective effect than their monotherapy. Combination of CM1 and GTE also reduced mitochondrial disruption and LIP content and ROS and TBARS production. In conclusion, the combination of CM1 and GTE exhibits protection against iron-induced oxidative stress in neuroblastoma cells.